2021
DOI: 10.3233/tub-200069
|View full text |Cite
|
Sign up to set email alerts
|

CA125: A superior prognostic biomarker for colorectal cancer compared to CEA, CA19-9 or CA242

Abstract: OBJECTIVES: The tumor stage represents the single most important prognostic factor for colorectal cancer (CRC), although more accurate prognostics remain much needed. Previously, we identified CA125 as an independent significant prognostic factor, which we have further validated along with CEA, CA19-9, and CA242 in a large cohort of CRC patients. METHODS: Using enzyme-linked immunosorbent assays, we analyzed preoperative serum samples in 322 CRC patients operated on between 1998 and 2003. RESULTS: Using the Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 15 publications
2
18
1
Order By: Relevance
“…Comparative studies using MUC16 and other tumor markers, such as carcinoembryonic antigen, have been conducted on colorectal adenocarcinomas [ 36 ]. MUC16 has been found to have potential relevance as a future serological marker (CEA) [ 37 ]. A correlation has been shown between the upregulation of MUC16 and the progression of pancreatic ductal adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Comparative studies using MUC16 and other tumor markers, such as carcinoembryonic antigen, have been conducted on colorectal adenocarcinomas [ 36 ]. MUC16 has been found to have potential relevance as a future serological marker (CEA) [ 37 ]. A correlation has been shown between the upregulation of MUC16 and the progression of pancreatic ductal adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of CA125 is associated with multiple systemic tumors (ovarian cancer, digestive system malignancy, tongue cancer, breast cancer, lung cancer, et al). A large number of studies [ 8 , 9 ] have reported that serum CA125 expression level varies in different ovarian cancer tissue types and surgical pathological stages, and the critical value of diagnosis is CA125 > 35 U/mL. A study showed that the serum CA125 in patients with ovarian epithelial cancer was significantly higher than that in germ cell tumor and sex cord-stromal tumor groups.…”
Section: Introductionmentioning
confidence: 99%
“… 47 For CEA, Björkman K et al investigated 322 staged I to IV CRC and found that CA125 was superior to CEA in predicting disease-specific survival (DSS). 48 In recent years, some authors have tried to combine ALB or CEA with other markers to further improve their prognostic efficacy. For ALB, Matsuoka et al collected 133 stage III CRC and explored the prognostic value of pre- and postoperative CAR, which was found to be an independent prognostic factor for recurrence-free survival and OS, but its AUC was only 0.63 and was the highest of the assessed markers (NLR, PLR).…”
Section: Discussionmentioning
confidence: 99%